Metal concentrations of simulated aerobic and anaerobic pilot scale landfill reactors - Bilgili, M. Sinan; Demir, Ahmet; Ince, Mahir; Ozkaya, Bestamin (ELSEVIER, 2007)
Leachate and solid waste samples from aerobic and anaerobic simulated landfill reactors operated with and without leachate recirculation were characterized in terms of metals such as Fe, Ca, K, Na, Cd, Cr, Cu, Pb, Ni, and Zn. Metal concentrations of aerobic landfill reactor leachate samples are always below the regulation limits. The higher concentrations in anaerobic landfill leachate samples decreased to regulation limits after the landfill becomes methanogenic. The effect of leachate recirculation is determined in anaerobic landfills more clearly than aerobic landfills. Metal precipitation resulted in a decrease in leachate metal content and an increase in solid waste metal content as expected. Result of the study show that the metal content of landfill leachate samples is not a major concern for both aerobic and anaerobic landfills. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: solid waste; landfill; aerobic landfill; anaerobic landfill; leachate; heavy metals; LEACHATE RECIRCULATION; HEAVY-METALS; DECOMPOSITION; Engineering; Environmental Sciences & Ecology